2007
DOI: 10.1007/978-1-4020-6191-2_15
|View full text |Cite
|
Sign up to set email alerts
|

Calcium signalling and cancer cell growth

Abstract: Abstract:Cancer is caused by defects in the mechanisms underlying cell proliferation and cell death. Calcium ions are central to both phenomena, serving as major signalling agents with spatial localization, magnitude and temporal characteristics of calcium signals ultimately determining cell's fate. There are four primary compartments: extracellular space, cytoplasm, endoplasmic reticulum and mitochondria that participate in the cellular Ca 2+ circulation. They are separated by own membranes incorporating dive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
62
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(64 citation statements)
references
References 141 publications
(159 reference statements)
2
62
0
Order By: Relevance
“…34,35 Bikle et al 35 showed that squamous cell carcinoma cell lines failed to respond to the prodifferentiating actions of vitamin D. Alterations of calcium signaling have also been linked to carcinomas of breast, colon, esophagus, liver, ovarian, and prostate origin. [27][28][29]33,36,37 These findings suggest a strong association between disruptions of calcium signaling and carcinogenesis and may provide targets for future therapeutic interventions by targeting of these pathways.…”
Section: Wnt/b-catenin Signalingmentioning
confidence: 96%
See 3 more Smart Citations
“…34,35 Bikle et al 35 showed that squamous cell carcinoma cell lines failed to respond to the prodifferentiating actions of vitamin D. Alterations of calcium signaling have also been linked to carcinomas of breast, colon, esophagus, liver, ovarian, and prostate origin. [27][28][29]33,36,37 These findings suggest a strong association between disruptions of calcium signaling and carcinogenesis and may provide targets for future therapeutic interventions by targeting of these pathways.…”
Section: Wnt/b-catenin Signalingmentioning
confidence: 96%
“…Calcium homeostasis is important in the orderly progression of the cell cycle, regulation of cell proliferation and growth, and apoptosis. 27 Deregulation of these intricate calcium signaling pathways has been implicating in tumorigenesis by evasion of apoptosis and the acquisition of self-sustaining growth signals. 27 The mechanisms of the deregulation of calcium signaling have been shown through T-type calcium channels, calcium pumps/exchangers, vitamin D, and calcium-sensing receptors.…”
Section: Wnt/b-catenin Signalingmentioning
confidence: 99%
See 2 more Smart Citations
“…The CaR is an essential part of an intricate network of Ca 2 þ -signalling pathways that control normal and cancer cell growth (Capiod et al, 2007). Depending on cell-specific coupling to appropriate G-proteins, activation of the CaR by elevated extracellular Ca 2 þ reduces the rate of cellular proliferation, as seen in human colon carcinoma (Kallay et al, 2003;Chakrabarty et al, 2005) or ovarian surface epithelial cells (Bilderback et al, 2002), but may also stimulate cell growth, as seen in malignant Leydig cells , and protect from apoptosis, for example, in prostate cancer cells (Lin et al, 1998).…”
Section: Cancermentioning
confidence: 99%